The SEO effect. Mapping the optimized landscape around controversial policy issues in Italy - Caroleo, Laura; Giorgi, Giulia; De Amicis, Camilla (Frontiers in Sociology, 2023)
This research investigates the use of search engine optimization (SEO) by political and non-political actors to amplify the visibility of search engine results. While there has been much theoretical speculation around the role of SEO techniques in boosting the ranking appearance of a website, few empirical studies have been undertaken to understand the extent to which SEO techniques are used to promote visibility online. This study takes Italy as a case study to map the information landscape around nine highly controversial issues during the Italian electoral campaign of 2022. Using a combination of digital methods and a tool detecting optimization in websites, our article aims at examining which actors employ SEO techniques to foster the circulation of their ideas and agendas around hot topics. Our analysis reveals that information channels, institutions, and companies are predominant, while political actors remain in the background. Contextually, data indicate that SEO techniques are employed by several recurrent editorial groups, company owners, and institutions. Ultimately, we discuss the impact of SEO techniques on the circulation and visibility of information around relevant policy issues, contributing to shaping and influencing public debate and opinion.